2004
DOI: 10.1152/jn.00031.2004
|View full text |Cite
|
Sign up to set email alerts
|

Precise Temporal Responses in Whisker Trigeminal Neurons

Abstract: . The ability of rats using their whiskers to perform fine tactile discrimination rivals that of humans using their fingertips. Rats must perform these discriminations rapidly and accurately while palpating the environment with their whiskers. This suggests that whisker-derived inputs produce a robust and reliable code, capable of capturing complex, high-frequency information. The first neural representation of whisker-derived stimulus information is in primary afferent neurons of the trigeminal ganglion. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
67
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 17 publications
17
67
1
Order By: Relevance
“…This resulted in broader ISI distributions that were not statistically distinguishable, but nevertheless had medians that correspond to the stimulus temporal frequency. We previously found similar variability in spike timing elicited in response to low frequency (<25 Hz) white-noise stimuli ( Jones et al 2004a( Jones et al , 2004b. Shoykhet et al (2000) also demonstrated that response latencies are more variable for low velocity whisker deflections.…”
Section: More Variable Responses At Low Frequenciessupporting
confidence: 75%
See 1 more Smart Citation
“…This resulted in broader ISI distributions that were not statistically distinguishable, but nevertheless had medians that correspond to the stimulus temporal frequency. We previously found similar variability in spike timing elicited in response to low frequency (<25 Hz) white-noise stimuli ( Jones et al 2004a( Jones et al , 2004b. Shoykhet et al (2000) also demonstrated that response latencies are more variable for low velocity whisker deflections.…”
Section: More Variable Responses At Low Frequenciessupporting
confidence: 75%
“…Previous studies have demonstrated that firing patterns of trigeminal ganglion neurons can phase-lock to high frequency stimuli (Gottschaldt and Vahle-Hinz 1981;Welker 1983a, 1983b;Lichtenstein et al 1990;Shoykhet et al 2000;Desch锚nes et al 2003;Jones et al 2004aJones et al , 2004bTimofeeva et al 2004). In these studies, individual whiskers were attached to a stimulating device and stimulated in isolation with precisely reproducible movements.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, Oswald et al (2007) showed that an ideal observer could distinguish different stimulus amplitudes using the amount of time between two consecutive spikes within a burst. As the value of the burst ISI was typically <10 ms and the time scales associated with the stimulus were in that study were greater than 16 ms, they showed that information about the stimulus is contained in the structure of the burst at time scales that are smaller than those contained in the stimulus, which constitutes a temporal code by definition (Theunissen and Miller 1995;Dayan and Abbott 2001;Jones et al 2004;Sadeghi et al 2007). Our previous results obtained in vivo did not find such strong correlations between burst and stimulus attributes (Avila Akerberg et al 2010).…”
Section: Do Bursts Contain Information About Sensory Stimuli In Theirmentioning
confidence: 90%
“…When rats sweep their whiskers across objects or textures, the spatial pattern is converted into a high-speed whisker vibration (the "vibrotactile signal"), whose dynamics are represented faithfully by first-order neurons in the trigeminal ganglion (Jones et al, 2004). Since the vibrotactile signal varies over time, it seems necessary to perform some sort of temporal integration of signals to extract features that carry information about the spatial configurations being palpated.…”
Section: Introductionmentioning
confidence: 99%